2015
DOI: 10.1016/j.watres.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Electro-osmotic-based catholyte production by Microbial Fuel Cells for carbon capture

Abstract: In Microbial Fuel Cells (MFCs), the recovery of water can be achieved with the help of both active (electro-osmosis), and passive (osmosis) transport pathways of electrolyte through the semi-permeable selective separator. The electrical current-dependent transport, results in cations and electro-osmotically dragged water molecules reaching the cathode. The present study reports on the production of catholyte on the surface of the cathode, which was achieved as a direct result of electricity generation using MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Carbonaceous materials used as cathode catalysts are generally based on graphene [352], [353], [354], [355] (that is probably the most expensive among all the carbonaceous materials), activated carbon [356], [357], [358], [359], [360], [361], [362], [363], carbon nanotubes [364], [365], carbon nanofibers [366], [367], [368], [369], simple or modified carbon black [233], [370], [371]. It was shown that high surface area conductive carbonaceous materials and nanometric pores enhance the ORR in neutral media [320], [331].…”
Section: Discussionmentioning
confidence: 99%
“…Carbonaceous materials used as cathode catalysts are generally based on graphene [352], [353], [354], [355] (that is probably the most expensive among all the carbonaceous materials), activated carbon [356], [357], [358], [359], [360], [361], [362], [363], carbon nanotubes [364], [365], carbon nanofibers [366], [367], [368], [369], simple or modified carbon black [233], [370], [371]. It was shown that high surface area conductive carbonaceous materials and nanometric pores enhance the ORR in neutral media [320], [331].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the same working principles applied to the MFC technology can be used, with the supply of external power, for producing useful products such as hydrogen [1,2], acetate [3,4], methane [5,6] as well as desalinate water [7,8]. Resource recovery and bio-sensing [9][10][11][12][13] are also highly active fields in the MFC research. Along with practical development of the technology, microorganisms involved in electricity generation have drawn a great deal of attention too.…”
Section: Introductionmentioning
confidence: 99%
“…In MFCs, cation species move through the membrane and accumulate in the aqueous cathodic chamber resulting in increased solution conductivity and pH . In air breathing cathodes, the electroosmotic drag was first observed in MFCs by Kim et al ., as the net water loss through the membrane that varied according to external resistance, that later led to the demonstration of the catholyte being accumulated as a result of the electrical current in wastewater operated MFCs . The composition of the catholyte primarily depends on the type of anolyte (feedstock) .…”
Section: Bioelectrochemical Systems Fed With Urinementioning
confidence: 99%
“…The ORR determines the physico-chemical properties of the catholyte by forming OH À as a product of the peroxide pathway [81] leading to local alkalisation of the cathode where the increase in current flow will lead to higher pH. [82][83] It was shown recently that the shift between the acidic ORR pathway and alkaline ORR pathway occurs around pH 11. [84][85] When protons or cations move through the membrane, water molecules accompany them or are actually "dragged".…”
Section: Catholyte Production During Microbial Fuel Cell Operationsmentioning
confidence: 99%
See 1 more Smart Citation